The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1748-717x-8-23
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of radiotherapy in the ongoing EORTC 22042–26042 trial for atypical and malignant meningioma: results from the dummy runs and prospective individual case Reviews

Abstract: BackgroundThe ongoing EORTC 22042–26042 trial evaluates the efficacy of high-dose radiotherapy (RT) in atypical/malignant meningioma. The results of the Dummy Run (DR) and prospective Individual Case Review (ICR) were analyzed in this Quality Assurance (QA) study.Material/methodsInstitutions were requested to submit a protocol compliant treatment plan for the DR and ICR, respectively. DR-plans (n=12) and ICR-plans (n=50) were uploaded to the Image-Guided Therapy QA Center of Advanced Technology Consortium serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…Interestingly, RTQA of this trial was excellent, with only 4.8% of the reviewed plans being non-protocol compliant. In the present study, RTQA was performed prospectively and each plan had to be uploaded in a secure server and reviewed prior to the initiation of the RT [15], using the same RTQA platform than the US trial [16]. Importantly, 18% of plans could not be prospectively analyzed as result of either corrupted or late data submission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, RTQA of this trial was excellent, with only 4.8% of the reviewed plans being non-protocol compliant. In the present study, RTQA was performed prospectively and each plan had to be uploaded in a secure server and reviewed prior to the initiation of the RT [15], using the same RTQA platform than the US trial [16]. Importantly, 18% of plans could not be prospectively analyzed as result of either corrupted or late data submission.…”
Section: Discussionmentioning
confidence: 99%
“…The target delineation definitions and dose constraints for organs at risk are detailed in Supplemental Tables 1 and 2. The quality assurance (RTQA) results of this study have been published previously [15]. Treatment after disease progression was left to the discretion of the treating physicians.…”
Section: Treatmentmentioning
confidence: 99%
“…As mentioned, the high incompliance with the 1 st patient randomized could be explained by the fact that no benchmark case exercise was conducted before patient accrual[21, 22]. However, the impact of benchmarking and prevention of future protocol non-compliance is questionable and there are conflicting results from other publications who address this issue[23].…”
Section: Discussionmentioning
confidence: 99%
“…Until the results of the EORTC 22042-26042 and Radiation Therapy Oncology Group 0539 studies [ 3 , 33 ] are available, there is no agreement on what radiation dose level should be prescribed for WHO grade II-III or recurrent meningioma; however, higher doses are believed to be more effective. Several studies examine the benefits of dose escalation – either by increasing the number of fractions with 3-dimensional (3D) conformal photon, photon-proton radiation therapy [ 3 , 11 , 12 ] or by using a sequential boost with photon 3D-conformal radiation therapy/IMRT [ 33 ], IMPT and carbon-ion radiation therapy [ 34 , 35 ]. A few studies demonstrated clinical feasibility of dose escalation combining photon and proton beams [ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%